Modeling the social-psychological mechanisms of employee turnover: An integrated environmental and organizational approach - Zeng Ge; Gerelmaa Jamsran; Narmandakh Dolgor (Environment and Social Psychology, 2025)
Employee turnover poses a growing challenge for organizations facing increasing environmental complexity and uncertainty. Prior research has largely examined turnover from isolated organizational or individual perspectives, overlooking the integrated role of environmental and organizational factors in shaping employees’social-psychological mechanisms. To address this gap, this study develops an integrated environmental–organizational framework to model the social-psychological drivers of employee turnover.Grounded in social exchange theory and conservation of resources theory, the model explains how external environmental pressures and internal organizational conditions jointly influence employees’ psychological states. Job satisfaction, organizational commitment, and psychological stress are examined as key mediating mechanisms linking environmental and organizational factors to turnover intention. Using survey data and structural equation modeling, the results indicate that environmental pressures increase turnover intention by intensifying psychological stress, while supportive organizational practices reduce turnover intention by enhancing job satisfaction and organizational commitment. Organizational support further buffers the negative psychological effects of environmental uncertainty.This study advances turnover research by clarifying its underlying social-psychological mechanisms and offers practical insights for turnover management.